SIBERNETIKA EMITAI ETZIONI DALAM MASYARAKAT ISLAM AKTIF PEDESAAN ERA GLOBAL - Tohari (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
The Islamic community is active is basically a social engineering attempts to turn anything into a Community citizen resistance in reaching for a better quality of life. The main target was the model for community development that put more emphasis on social life. How social functions can walk normally, the social forbidden can be removed. So individual pious who have achieved can impact more evident in social pious. Active in rural communities is seen among them wholesale workers (homeworking) or the volume of work at home is a hireling labor done at home on the basis of the unit of work done. This job is order a brokers and throw the result of stores or directly to consumers. Cases have been mentioned was partly example of islamic community active global era. The boarding school (Pesantren) economic empowerment, street children, industry workers home and so on. The theoretical models was used are sibernetik. Sibernetik is a model the basis for the general theory or the modern system theories. Modern history by aziz al-azmeh Characterized by globalization west global dominate. Globalization show rapid developments in the field of communication, technology, transportation and information who made the world more narrowly because everything more easily accomplished.